2013
DOI: 10.3390/s130404067
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Quality Analysis of a Fiber Optic Refractive Index Sensor Created by CO2 Laser Machining

Abstract: This study investigates the CO2 laser-stripped partial cladding of silica-based optic fibers with a core diameter of 400 μm, which enables them to sense the refractive index of the surrounding environment. However, inappropriate treatments during the machining process can generate a number of defects in the optic fiber sensors. Therefore, the quality of optic fiber sensors fabricated using CO2 laser machining must be analyzed. The results show that analysis of the fiber core size after machining can provide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The choice of the length of the unclad fiber is based on an optimization study as reported previously [ 23 ]. The fabrication quality analysis for the laser-processed optical fiber sensors follows a method as previously reported [ 38 ]. The quality assurance method provides superior quality verification of the materials properties of the optical fiber sensors to eliminate any concerns regarding the fiber damage in the unclad region and the subsequent change of the refractive index in that area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the length of the unclad fiber is based on an optimization study as reported previously [ 23 ]. The fabrication quality analysis for the laser-processed optical fiber sensors follows a method as previously reported [ 38 ]. The quality assurance method provides superior quality verification of the materials properties of the optical fiber sensors to eliminate any concerns regarding the fiber damage in the unclad region and the subsequent change of the refractive index in that area.…”
Section: Methodsmentioning
confidence: 99%
“…The optical fiber-based PPR sensor, named fiber optic particle plasmon resonance (FOPPR) sensor, is based on immobilization of AuNPs on the unclad section of an optical fiber to form a sensing fiber [ 23 , 25 ]. As the quality of the exposed fiber core surface and the coverage of AuNPs on the fiber core surface will influence the sensitivity of the FOPPR sensor, fiber surface quality analysis has been discussed in literature [ 38 ]. However, the effects of surface coverage and surface distribution of AuNPs on the sensitivity of PPR sensors are not trivial since direct tools to measure the surface coverage and surface distribution of AuNPs on the fiber core surface are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (methyl methacrylate) (PMMA) was used for manufacturing multi-microchannel microfluidic biochip. The multi-microchannel biochip was composed of two poly (methyl methacrylate) (PMMA) plates, a cover and a bottom plate, with dimensions of 40 mm (width) × 30 mm (length) × 4 mm (thickness) and fabricated by using a CO 2 laser [33]. The bottom plate contained multi-microchannels (five microchannels) with a depth of 1000 µm and a width of 1000 µm.…”
Section: Reagents and Materialsmentioning
confidence: 99%